2016
DOI: 10.1016/j.fsigen.2016.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Genetic mapping of 15 human X chromosomal forensic short tandem repeat (STR) loci by means of multi-core parallelization

Abstract: Typing of X chromosomal short tandem repeat (X STR) markers has become a standard element of human forensic genetic analysis. Joint consideration of many X STR markers at a time increases their discriminatory power but, owing to physical linkage, requires inter-marker recombination rates to be accurately known. We estimated the recombination rates between 15 well established X STR markers using genotype data from 158 families (1041 individuals) and following a previously proposed likelihood-based approach that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…Obviously, linked markers are more prone to be in LD. Segregation analyses in one or multi generation family studies were performed, aiming to estimate recombination rates between X-STRs of interest through proper bioinformatic pipelines that take into account the possibility of mutation ( Nothnagel et al, 2012 ; Diegoli et al, 2016 ; Bini et al, 2019 ), but population-based studies, as HapMap project ( The International HapMap Consortium, 2007 ), can also be considered ( Phillips et al, 2012 ). Mapping functions as Haldane’s ( Haldane, 1919 ) or Kosambi’s ( Kosambi, 1944 ) are used to convert genetic distances between markers in recombination rates.…”
Section: The Use Of X-chromosomal Markers In (Complex) Kinship Testinmentioning
confidence: 99%
“…Obviously, linked markers are more prone to be in LD. Segregation analyses in one or multi generation family studies were performed, aiming to estimate recombination rates between X-STRs of interest through proper bioinformatic pipelines that take into account the possibility of mutation ( Nothnagel et al, 2012 ; Diegoli et al, 2016 ; Bini et al, 2019 ), but population-based studies, as HapMap project ( The International HapMap Consortium, 2007 ), can also be considered ( Phillips et al, 2012 ). Mapping functions as Haldane’s ( Haldane, 1919 ) or Kosambi’s ( Kosambi, 1944 ) are used to convert genetic distances between markers in recombination rates.…”
Section: The Use Of X-chromosomal Markers In (Complex) Kinship Testinmentioning
confidence: 99%
“…Previous studies have demonstrated that loci inside each of the four X-STR linkage groups show reduced, but non-zero recombination rates [27]. In addition, recombination between linkage groups is less than 50% [7,28,29]. In fact, Diegoli and Rohde [7] argues against a simple model of independent X chromosomal linkage groups for these reasons.…”
Section: Linkage Disequilibrium Analysis and Haplotypic Structurementioning
confidence: 99%
“…In addition, recombination between linkage groups is less than 50% [7,28,29]. In fact, Diegoli and Rohde [7] argues against a simple model of independent X chromosomal linkage groups for these reasons.…”
Section: Linkage Disequilibrium Analysis and Haplotypic Structurementioning
confidence: 99%
See 2 more Smart Citations